National Security Issues : Northeast India perspectives - Ahmed, Abu Nasar Saied; Ahmed, Abu Nasar Saied; Omeo Kumar Das Institute of Social Change and Development (Gauhati, India); Indian Council of Social Science Research (New Delhi : Omeo Kumar Das Institute of Social Change and Development and Akansha Pub. House, 2007)
Contributed articles presented at a seminar by Omeo Kumar Das Institute of Social Change and ICSSR.
Includes bibliographical references and index.
Keywords: National security -- India, Northeastern -- Congresses